Time series and panel data econometrics - Pesaran, M. Hashem, 1946- (Oxford : Oxford University Press, 2016)
This work describes and illustrates many advances that have taken place in a number of areas in theoretical and applied econometrics over the past four decades.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on January 26, 2016).
Keywords: Econometrics; Macroeconomics -- Mathematical models